Are the Complication Rates for the Open Approach in the Surgical Treatment of Bladder Stones Higher Than Rates for Endoscopic Approaches? A Comparative Multivariate Analysis Study - Çetin Demirdağ; Oktay Özman; Sinharib Çitgez; Berin Selçuk; Bülent Önal; Zübeyr Talat (Journal of Urological Surgery, 2018)

(untitled)
Objective:To compare the effectiveness, safety and complication rates of open vs endoscopic approach for bladder stone surgery and investigate the predictive factor for success and complication rate in patients with bladder stone.Materials and Methods:The records of 128 patients, who underwent stone surgery between November 2010 and June 2017, were analyzed. The patients were divided into two groups according to surgical approach as endoscopic or open group. Duration of surgery and catheterization and length of hospital stay were recorded. Multivariate analyses were done using logistic regression test to determine the risk factors for complications.Results:A total of 130 procedures were performed in 128 patients included in the study. Of them, 93 were treated via endoscopic approach and 37 via open approach. The overall success rate in endoscopic and open groups was 92.5% and 100%, respectively (p=0.44). Increased age, type of surgical approach and using lithotripsy were found to be risk factors for complications in univariate analysis. Only the type of surgery was found to be an independent risk factor for complications in multivariate analysis (p=0.006).Conclusion:Open and endoscopic approaches showed similar effectiveness in patients with bladder stone. The only significant risk factor for complications was the type of surgical approach.